Theorising an Omnipresent Concept. Memory as a Thickening Factor of Populism - Mazzini, Mateusz (Acta Poloniae Historica, 2024)
Within various fields of social sciences, populism is being constantly re-conceptualised to create a possibly most holistic definition of the phenomenon, one which would encompass all of its structural features and allow it to be applied to the largest number of empirical manifestations. Nonetheless, across different disciplines a growing consensus gains traction to define populism through the framework of ideology. As such, populism is understood as possessing a capability to attach itself to more powerful ideological concepts – nationalism, socialism, fascism. Thus, the central question in the study of populism as ideology needs to focus on the mechanics of strengthening populism in a given case. What makes one populism more radical than another? Using Freeden’s ideational approach and Mudde’s work on factors influencing intensity and efficiency of populism, this paper argues that the perception of the past in a given community, constructed through collective memory policies and expressed by means of historical revisionism, works as a ‘thickening agent’ fostering electoral success and increasing political durability of populist governance. Although seeking to create primarily a theoretical contribution, it will also encompass evidence of that modality from studying collective memory policies under Poland’s Law and Justice Party rule between 2015 and 2019.